ACTIVE LABOR MARKET POLICIES IN KOSOVO FROM A STATISTICAL POINT OF VIEW AND WITH THE FOCUS ON YOUTH - Bashkim Bellaqa (European Scientific Journal, ESJ, 2012)
The purpose of this article is to analyze the implementation of labor market policies as well as labor market statistics for the youth in Kosovo. In this article factors influencing the employment and unemployment trends of youth in Kosovo are analyzed. The article is developed based on literature published by local and international institutions regarding policies and statistical analysis related to the labor market of the youth in Kosovo. Kosovo is characterized by high level of unemployment which is around 45.7%, while for the age group 15 to 24 unemployment rate is about 73%-high by any international standard. This high unemployment rate presents not only social and economic problem but also a political problem. Kosovo is faced with a high number of young people entering into the labor market, around 25,000 people entering the labor market every year and around 6,000 people leaving the labor market. Although Kosovo has had a positive GDP growth in the previous years, this increase has not been sufficient to improve the level of employment trends especially for the youth-those between 15 to 24 years old. To address this high unemployment rate Kosovo government should tailor labor market policies that create a friendly environment for the business start-ups and provide training programs to increase professional capacities according to the needs of the labor market.